Antiplasmodial Activity of The Low Molecular Weight Compounds from Streptomyces sp. GMR22 - Tarsa Ruli Tambunan; Jaka Widada; Ema Damayanti; Tutik Dwi Wahyuningsih; Mustofa Mustofa (Universitas Gadjah Mada, 2020)
Low molecular weight (LMW) antiplasmodial compounds isolated from bacteria, particularly Streptomyces have not been widely reported. This study aimed to identify LMW compounds from Streptomyces sp. GMR22 as antiplasmodial. Isolation of the LMW compounds from the supernatant of fermentation culture using solvent of n-hexane:ethylacetate (EtOAc) (85:15v/v)and identified using gas chromatography-mass spectrometry (GC-MS). Antiplasmodial assay of n-hexane:EtOAc extract was carried out in vitro against P. falciparum (3D7). Parasitemia percentage obtained through microscopic observations and 50% inhibitory concentration (IC50) obtained through probit analysis. The antiplasmodial confirmation test was done by flow cytometry using SYBR Green I for Plasmodium DNA and anti-human CD235a for erythrocytes. The LMW compounds were investigated using SwissADME for drug-likeness. n-Hexane:EtOAc extract contained 21 LMW compounds from alcohol, hydrocarbon, ester, aromatic/diester, diester, fatty acid, and triester classes, which possessed moderate antiplasmodial activity with an IC50 value of 38.61 ± 19.06 µg/mL. Confirmation by flow cytometry analysis showed that the extract at 50 µg/mL exhibited antiplasmodial activity based on a decreased Plasmodium DNA intensity as compared to the control group. The result of drug-likeness screening obtained that 3 LMW compounds were drug-likeness, namely phenylethyl alcohol, ethyl citrate, and di-n-butyl phthalate. Streptomyces sp. GMR22 produced LMW compounds as antiplasmodial, and further study was needed for identification of antiplasmodial active compounds.